KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMK DALAM PEMBELAJARAN DISCOVERY LEARNING BERDASARKAN GAYA BELAJAR SISWA - Arezqi Tunggal Asmana (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2021)
The problem solving abilities of students who are still lacking need to be reviewed further based on Discovery Learning and student learning styles. The subjects of this study were 15 students of class X Accounting SMK NU 05 Babat. Data collection was carried out through learning style questionnaires, problem solving ability tests, and interview guidelines. The subjects of this study were identified the type of learning style using Kolb's learning style questionnaire. Data about problem solving abilities were analyzed from the results of problem solving ability tests then described with the results of interview data. 8 students consisting of 2 students in each type of learning style were selected to interview their problem solving abilities. The results of this study indicate that of 15 students of class X SMK NU 05 Babat shows that: 1) there are 2 students who have a converger learning style, 6 students have a diverger learning style, 3 students have an accommodator learning style, and 4 students have an assimilator learning style; 2 ) most diverger students in class X Accounting SMK NU 05 Babat, rather than converger, accommodator, assimilator and converger students; 3) assimilator students are able to understand theory; 4) good accommodator students in carrying out plans; 5) students are diverger with creative and imaginative abilities; 6) converger students are good when there is a single correct solution of a problem and they can be centered on a particular problem or situation.